Review of the Short-Winged Mold Beetles (Coleoptera, Staphylinidae, Pselaphinae) of the Crimea (Ukraine) - Krivosheyev, R.E. (Вестник зоологии, 2013)
Twenty species of the Pselaphinae (Coleoptera, Staphylinidae) are recorded for the first time from Crimean Peninsula. Bryaxis moczarskii (Winkler, 1911) is redescribed and illustrated for the first time after its original description. Brachygluta guillemardi (Saulcy, 1876), Bryaxis longulus (Kiesenwetter, 1849) and Claviger colchicus Motschulsky, 1837 are recorded for the first time from Ukraine. In total, 34 species of ten genera and one unrecognizable nominal species are recorded from Crimea. Впервые для Крымского полуострова указаны 20 видов ощупников. Приведено иллюстрированное переописание Bryaxis moczarskii (Winkler, 1911). Brachygluta guillemardi (Saulcy, 1876), Bryaxis longulus (Kiesenwetter, 1849) и Claviger colchicus Motschulsky, 1837 отмечены впервые в фауне Украины. В целом из Крыма приведены 34 вида из 10 родов и один не подлежащий идентификации номинальный вид.